THEORETICAL CONSIDERATIONS OF PRICE STABILITY AS PART OF THE FINANCIAL STABILITY - Magdalena RĂDULESCU; Marinela TANASCOVICI (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2012)
Currently there are many authors who consider that the only objective of the central bank should be the price stability and between the respective objective and financial stability there is incompatibility. As far we are concerned, we subscribe the idea that between price stability and financial stability there are complementarities. And a strong argument in the favour of this position is also historical. Actually, many older or newer facts show that banking crises were often caused by the unfavourable macroeconomic situation coupled with the bad macroeconomic policies carried by the authorities. But, a monetary policy that aims the price stability reduces this risk. The truth is that the central banks have a series of tools that allow them to act for achieving both the objective of price stability, and that of the stability of financial sector. Although the financial stability is not, usually, an explicit objective for the modern central bank, the systematic financial instability can cancel their performances in achieving their major final objective: the price stability. Being that, because of the need that it creates to inject additional liquidity into the banking system, a crisis of the banking sector may directly affect the monetary stability. Here the mentioned complementarities arise between price stability and financial stability, although the achievement of the first does not necessarily involve the assurance of the last.